PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA GURU SMA PATRA DHARMA BALIKPAPAN - Pasapan, Eufrasia; Yusuf , Tamzil; Yuliani , Tutik (Jurnal GeoEkonomi, 2024)
This research aims to determine the influence of the work environment, motivation and work discipline on the job satisfaction of teachers at Patra Dharma Balikpapan High School. The total sample tested was 52 teachers with a classification of 36 permanent teachers and 16 honorary teachers. The techniques used are instrument testing, classical assumption testing, multiple linear regression analysis testing, hypothesis testing